Hydration and properties of blended cement system incorporatiing aerogel - Mohd Ikram Nul Hakim Baharom, 1992-, author; Che Rozid Mamat, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2015